Directed Self-Assembly of Trimeric DNA-Bindingchiral Miniprotein Helicates - Gómez-González, Jacobo; Peña, Diego G.; Barka, Ghofrane; Sciortino, Giuseppe; Maréchal, Jean-Didier; Vázquez López, Miguel; Vázquez, M. Eugenio (Frontiers in Chemistry, 2018)
We propose that peptides are highly versatile platforms for the precise design of supramolecular metal architectures, and particularly, for the controlled assembly of helicates. In this context, we show that the bacteriophage T4 Fibritin foldon (T4Ff) can been engineered on its N-terminus with metal-chelating 2,2′-bipyridine units that stereoselectively assemble in the presence of Fe(II) into parallel, three-stranded peptide helicates with preferred helical orientation. Modeling studies support the proposed self-assembly and the stability of the final helicate. Furthermore, we show that these designed mini-metalloproteins selectively recognize three-way DNA junctions over double-stranded DNA.